تفعيل آليات تسليم المجرمين في إطار المنظمة الدولية للشرطة الجنائية - قارة, آمال (جامعة الوادي University of Eloued, 2018)
ملخـــــص: من النتائج المترتبة على مبدأ السيادة الاقليمية للدول انه لاوجود لشرطة عالمية يمتلك اعضاؤها صلاحية التحري عبر العالم عن الجرائم والتحري عن ادلتها والقبض على مرتكبيها، ومع ذلك فان الملاحظ في هذا الخصوص ان المجتمع الدولي قد ادرك خصوصية التعاون الدولي في اطار تسليم المجرمين بشكل خاص وفي مكافحة الجريمة بشكل عام، وتبلور ذلك في ظهور العديد من المنظمات العالمية التي تعنى بذلك، وتعد المنظمة الدولية للشرطة الجنائية من ابرز نماذج المنظمات العالمية في هذا الاطار، مع عدم انكار دور الاجهزة المتخصصة في مجال مكافحة الجريمة، وقد تناولنا من خلال هذا المقال اليات التعاون الشرطي الدولي في اطار تسليم المجرمين، مع بيان الصعوبات التي تواجه عمل منظمة الانتربول في ميدان مكافحة الجريمة لاسيما الجريمة المنظمة والحلول المقترحة. Abstract : One of the consequences of the principle of the territorial sovereignty of States is that there is no universal police force; whose members have the authority to investigate, search for evidence and arrest the perpetrators of crimes throughout the world. It is noted, however, that the international community has recognized the specificity of international cooperation in the context of extradition in particular and in the fight against crime in general.The International Criminal Police Organization is one of the most prominent models of international organizations in this regard, without denying the role of the specialized agencies in the field of combating crime. This article discusses the mechanisms of international police cooperation In the framework of extradition, with a description of the difficulties facing Interpol’s work in the field of crime control, especially organized crime and proposed solutions.
Keywords: انتربول- تسليم مجرمين- جريمة منظمة- نشرات- أمر بالقبض دولي; Interpol - Extradition - Organized crime - publications - International arrest warrant .